Low temperature mixed spin state of Co³⁺ in LaCoO₃ evidenced from Jahn–Teller lattice distortions - Gnezdilov, V.; Choi, K.-Y.; Pashkevich, Yu.; Lemmens, P.; Shiryaev, S.; Bychkov, G.; Barilo, S.; Fomin, V.; Yeremenko, A.V. (Физика низких температур, 2006)
One- and multi-phonon excitations of the single crystalline LaCoO₃ were studied using Raman spectroscopy in the temperature region of 5–300 K. First-order Raman spectra show a larger number of phonon modes than allowed for the rhombohedral structure. Additional phonon modes are interpreted in terms of activated modes due to lattice distortions, arising from the Jahn–Teller (JT) activity of the intermediate-spin (IS) state of Co³⁺ ions. In particular, the 608-cm⁻¹ stretching-type mode shows anomalous behavior in peak energy and scattering intensity as a function of temperature. The anomalous temperature dependence of the second-order phonon excitations spectra is in accordance with the Franck–Condon mechanism that is characteristic for a JT orbital order.